Efektivitas Penambahan Astaxanthin pada Pakan Komersil untuk Meningkatkan Kecerahan Warna, Pertumbuhan dan Sintasan Ikan Komet (Carassius auratus) - Phonna, Zulfahmi; Febri, Suri Purnama; Hanisah, Hannisah (MAHSEER: Jurnal Ilmu-Ilmu Perairan dan Perikanan, 2022)
This study aims to determine the effectiveness of adding Astaxanthin to commercial feed to increase color brightness, growth and survival rate of comet fish. This study used a completely randomized design (RAL) with 4 treatments and 3 replications. The treatment given was (P1) = without Astaxanthin; (P2)= 250 mg Astaxanthin /1/2 kg of feed; (P3)= 500 mg Astaxanthin /1/2 kg feed; (P4) 750 mg Astaxanthin/1/2 kg feed. Parameters observed were color brightness, absolute length growth rate, absolute weight growth, daily growth rate, survival rate, and FCR. The results showed that the effectiveness of adding Astaxanthin to commercial feed did not have a significant effect (Fhit<Ftab) on increasing color brightness, absolute length growth, daily growth rate, survival rate and had a significant effect (Fhit>Ftab) on absolute weight growth, FCR. The additional dose of Astaxanthin P4 (750 mg) was the best dose for absolute weight growth and FCR.